Religious salience and adolescent substance use revisited: the role of beliefs in moral relativism and moral contextualism - Lehmann, Peter S. (Journal of crime and justice, 2025)
Much prior research has established an inverse relationship between religiosity and delinquency among adolescents, with particularly noteworthy effects observed for illicit substance use. These patterns correspond with the expectations of social bond theory and situational action theory, which posit that commitment to conventional religious norms can reduce youths’ exposure to, and inform their experiences with, delinquent opportunities. However, little empirical attention has been given to youths’ beliefs surrounding the nature of morality itself, which are theoretically expected to moderate the protective effects of religious salience. Specifically, while religious salience might have a general controlling influence on adolescents’ use of cigarettes, alcohol, and marijuana, holding beliefs in moral relativism (i.e., the absence of definitive rights and wrongs) or moral contextualism (i.e., that rights and wrongs are fluid and dynamic) might weaken these inhibiting effects. Using data on a nationally representative sample of adolescents from the National Study of Youth and Religion (N = 3,170), this study’s analyses reveal that the association between religious salience and substance use is conditioned by moral contextualism but not moral relativism, though this interactive relationship is found only for alcohol use and drunkenness.